A study in the competitive dynamics of Chinese mobile phone corporations ? from a value chain perspective. (21st February 2008) - Chang, Ching-Yi; Fu, Hsin-Pin; Wang, Fanghua
Since the liberalisation of the telecommunications industry in mainland China during the early 1980s, the mobile phone industry has seen significant developments, registering substantial increases in the number of users and manufacturers, and in production capacity. However, based on market share, International Brands (IBs) continue to dominate the mobile phone market, indicating that Domestic Brands (DBs) lag behind in the Chinese market. Therefore, this paper focuses on the top five DBs that are able to compete with IBs in the Chinese market, to understand their strengths and weaknesses and then to analyse their competitiveness from a value chain perspective using the Analytic Hierarchy Process (AHP). Questionnaires were issued to experts familiar with the DBs in Shanghai, China, and each corporation was weighted based on their capabilities, using the AHP analysis. This paper presents recommendations for the individual companies with respect to their future management and strategic planning.